Firms, boards and gender quotas comparative perspective - Engelstad, Fredrik, 1944-; Teigen, Mari. (Bingley, U.K. : Emerald, 2012)
During the last decade gender equality in business life has become a hot topic. One impetus is the recent reform in Norway, prescribing gender quotas to the boards of directors of public companies. Shortly after the Norwegian reform was enacted, several other European countries have adopted similar reforms. This is the only volume where this gender quota reform is thoroughly discussed from an economic, political and philosophical point of view. It looks at whether the economic performance of companies is influenced, positively or negatively. The reasons why it has been embraced in some countries and rejected in others are analyzed. Moreover, viability of the gender quota reform is assessed by comparisons to other political interventions in business life in Scandinavia, of which some have been a failure whereas others have shown themselves as successful. This specific reform also serves as a backdrop to other themes related to gender and business. This volume provides a broad comparative study of the access of women to top positions in business in Europe. It also gives detailed discussions of gender relations in family businesses both in East Asia and in Europe.
ch. 1. Top down or bottom up? : a cross-national study of vertical occupational sex segregation in 12 European countries / Andrea Schäfer, Ingrid Tucci, Karin Gottschall -- ch. 2. Modes of familism : gender, family capitalism and family culture / Jorun Solheim, Ragnhild Steen Jensen -- ch. 3. Family, labour market structures and the dynamics of self-employment in three Asian countries : gender differences in the self-employment entry in Japan, Korea and Taiwan / Hirohisa Takenoshita -- ch. 4. Gender quotas on corporate boards : on the diffusion of a distinct national policy reform / Mari Teigen -- ch. 5. Why gender quotas in company boards in Norway : and not in Sweden? / Vibeke Heidenreich -- ch. 6. Feminism without gender? : arguments for gender quotas on corporate boards in Norway / Hilde Bjørkhaug, Siri Øyslebø Sørensen -- ch. 7. Women on boards of directors and firm performance : evidence from Denmark and Norway / Harald Dale-Olsen, Pål Schøne, Mette Verner -- ch. 8. Limits to state intervention into the private sector economy : aspects of property rights in social democratic societies / Fredrik Engelstad.
Print version record
Keywords: Social Science -- Discrimination & Race Relations; Social Science -- Gender Studies; Social Science -- Sociology -- General; Gender studies: women; Social research & statistics; Sex role in the work environment; Gender identity in the workplace